OPTIMIZATION OF ISLAMIC CHARACTER EDUCATION THROUGH PAI LEARNING IN SMP MUHAMMADIYAH 07 MEDAN - Fachri Dahnial; Selamat Pohan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to optimize Islamic character education through Islamic Religious Education (PAI) learning at SMP Muhammadiyah 07 Medan. With the challenges of globalization that erode Islamic character values, it is important to explore effective learning methods. Through a qualitative approach, this study analyzes the implementation, supporting factors, and obstacles in Islamic character education. The results of the study indicate that school commitment and parental involvement are very influential in creating a conducive learning environment. However, there are obstacles such as lack of resources and differences in student backgrounds that affect the application of character values. Therefore, the proposed strategy includes the development of innovative and collaborative learning methods between schools, parents, and the community. This study is expected to provide recommendations for the development of more effective curriculum and learning methods in Islamic character education.